1988
DOI: 10.1021/bi00402a027
|View full text |Cite
|
Sign up to set email alerts
|

Reductive methylation of lysine residues in acidic fibroblast growth factor: effect on mitogenic activity and heparin affinity

Abstract: Reductive methylation of bovine brain derived acidic fibroblast growth factor (aFGF) with formaldehyde and sodium cyanoborohydride reduces its capacity to stimulate mitogenesis in Balb/C 3T3 cells, and this correlates with the modification of less than 3 of its 12 lysine residues. Fractionation of methylated aFGF on immobilized heparin shows that the affinity of the modified mitogen for heparin is also decreased substantially. The capacity of methylated mitogen of low heparin affinity (LA-aFGF) to stimulate mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
45
0
4

Year Published

1989
1989
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 34 publications
7
45
0
4
Order By: Relevance
“…A large number of functional studies (involving chemical modification, point mutations, deletion mutations, homologous substitution mutations, and peptide-binding competition studies) in combination with analytical ultracentrifugation, surface plasmon resonance, and affinity chromatography validate the above structural data. [42][43][44][45][46] Heparin binds a specific cluster of basic residues with positive charge density and comprised mostly from the first b-hairpin and the last two-thirds of the third trefoil-fold subdomain (Fig. 3, lower panel).…”
Section: Discussionmentioning
confidence: 99%
“…A large number of functional studies (involving chemical modification, point mutations, deletion mutations, homologous substitution mutations, and peptide-binding competition studies) in combination with analytical ultracentrifugation, surface plasmon resonance, and affinity chromatography validate the above structural data. [42][43][44][45][46] Heparin binds a specific cluster of basic residues with positive charge density and comprised mostly from the first b-hairpin and the last two-thirds of the third trefoil-fold subdomain (Fig. 3, lower panel).…”
Section: Discussionmentioning
confidence: 99%
“…62 Harper and Lobb 42 recently reported that reductive methylation of less than three lysines in acidic fibroblast growth factor (FGF) significantly reduced its heparin affinity, growth factor receptor affinity, and ability to stimulate mitogenesis in Balb/C 3T3 fibroblasts. Lys-118 was the primary site of dimethylation, and Lys-118 and -112 were the major sites of monomethylation.…”
Section: Hc-ii Contains the [-X-b-b-b-x-x-b-x-] Consensus Given By mentioning
confidence: 99%
“…34 Based on helical wheel diagrams, 35 acidic FGF shows potential to form a-helix. Chemical modification of lysine-112 and lysine-118 by reductive methylation 42 might possibly destabilize the charge interaction with heparin and hence the helical conformation.…”
Section: Molecular Modeling Of Heparin Bindingmentioning
confidence: 99%
“…Reductive methylation of lysine residues in aFGF has previously suggested the conserved Lys 125 as having a role in heparin binding (Harper & Lobb, 1988). Sitedirected replacement of Lys 125 with glutamic acid also causes significant reduction in heparin binding (Burgess et al, 1990b).…”
Section: Heparin Bindingmentioning
confidence: 99%